EKSEKUSI HAK TANGGUNGAN PERBANKAN SYARI’AH (ANALISIS PERKARA 001/Pdt/Eks/2012/PA.Min DI PENGADILAN AGAMA MANINJAU) - Adil Fakhru Roza (Tamwil, 2017)
This research is a law research (legal research), and the object of the research is a Shari'ah economic case document for case No. 001/Pdt/Eks/2012/PA.Min., in Pengadilan Agama Maninjau. From these studies the authors found that in the process of execution of this case, the court has attempted to implement in accordance with the provisions of the legislations force in Indonesia and the object of the dispute has been submitted to the winner of the auction, executed forced out of the object of execution, although the execution still in debating about the capacity and authority of religious courts in carrying out executions Hak Tanggungan for islamic banking in Indonesia.